THE EXPLORATION OF USING E-SCAFFOLDING IN SOLVING PHYSICS PROBLEM - Setiawan, Trisno; Koes, H Supriyono; Wartono, . (PEOPLE: International Journal of Social Sciences, 2018)
The ability of problem solving is one of the important ability which is had by student. In physics, problem solving use to solve physics exercise not only low level exercise but also high level exercise. E-Scaffolding is the help which is given to the student as online which is integrated in the website. This research aims to see how far the effectivity E-Scaffolding which is given can help student to solve the physics exercise. The research samples are five students of class X science 3 senior high school 2 Malang 2016/2017. The taken technique is purposive sampling. The data is gotten from the student’s exercise recording in the website then it is sent to the researcher’s email. Data is analyzed qualitatively. In thus research, E-Scaffolding which is use is procedural scaffolding and strategy scaffolding. Procedural scaffolding and strategy scaffolding use question prompts but in strategy scaffolding adds choice of answer which is chosen by student. The result of the research shows that E-Scaffolding can help to give the student’s indication in solving the physics problem. The student who is correct on procedural scaffolding and strategy scaffolding tends be able to solve physics exercise correctly and otherwise. These both scaffoldings can be the alternative to the teachers in helping students to solve the physics question in medium level and high level.